2020
DOI: 10.1249/mss.0000000000002454
|View full text |Cite
|
Sign up to set email alerts
|

Novel CPET Reference Values in Healthy Adults: Associations with Physical Activity

Abstract: Purpose Cardiopulmonary exercise testing (CPET) is an important measurement in clinical practice, and its primary outcome, maximal oxygen uptake (V˙O2peak), is inversely associated with morbidity and mortality. The purposes of this study are to provide CPET reference values for maximal and submaximal parameters across the adult age spectrum of a healthy European cohort, to compare V˙O2peak values with other reference data sets, and to analyze the associations between physical activity (PA) levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…In contrast, 50 th centiles for the male VE/VCO2 slopes reported in the current study (treadmill protocol) ranged from 26.31 to 29.46 for 30 years to 60-year-old males respectively. A similar contrast is observed with female VE/VCO2 slopes, The 50 th centiles for the female VE/VCO2 slope scores reported by Wagner et al [23] ranged from 34.0 to 36.5 (30 years to 60 year old females respectively). The 50 th centiles for the female VE/VCO2 slope scores reported in the current study (treadmill) ranged from 27.76 to 29.97 for 30 years to 60-year-old females respectively.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In contrast, 50 th centiles for the male VE/VCO2 slopes reported in the current study (treadmill protocol) ranged from 26.31 to 29.46 for 30 years to 60-year-old males respectively. A similar contrast is observed with female VE/VCO2 slopes, The 50 th centiles for the female VE/VCO2 slope scores reported by Wagner et al [23] ranged from 34.0 to 36.5 (30 years to 60 year old females respectively). The 50 th centiles for the female VE/VCO2 slope scores reported in the current study (treadmill) ranged from 27.76 to 29.97 for 30 years to 60-year-old females respectively.…”
Section: Discussionsupporting
confidence: 73%
“…Comparing the centile curves reported by W agner et al [ 23 ] using bicycle ergometry with those reported in the current study using a treadmill protocol, we detected large differences. The 50th centiles for the male V ʹ E / V ʹ CO 2 slopes reported by W agner et al .…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Peak oxygen uptake (peakVO 2 ) was defined as the highest 30-s average ofVO 2 at any point during the test.VO 2 off-kinetics were assessed from the active recovery period that directly followed the incremental phase of the CPET. A complete description of the CPET is described by Wagner et al (2020).…”
Section: Cardiovascular Endurance Domainmentioning
confidence: 99%